The contents of contemporary professional education in the books of Social and national education (developed) for the basic intermediate stage in Jordan - Al-Btoush, Anam Abdel Salam (Journal of Educational and Psychological Sciences, 2020)
The study aimed at identifying the extent to which Social and national education textbooks developed for the basic intermediate stage in Jordan included the contents of contemporary professional education. The study tool was developed in a list representing the contents of contemporary professional education. It consisted of three) fields: agricultural, industrial, commercial; (16) Guaranteed. The content analysis method has been used where the wholesale and semi-sentence and unit of analysis have been taken, down to the quantitative data of the duplicates and percentages. The results revealed The following: The agricultural field got 43.0%, the commercial field got 33.5%, while the industrial field got 23.4%, and this confirms that the books did not take into consideration the contents of contemporary professional education and the principle of sequence, and did not adopt a clear methodology, but rather a traditional, random curve in dealing with the contents of the study. The study recommended the following: Reviewing the content of the books of Social and national education developed for the basic intermediate stage in Jordan including the contents of contemporary professional education, and the extent to which they respect the principles of integration and sequence and the principles of self-learning and structural in addressing them.